EVALUASI PEMBERDAYAAN JURU PEMANTAU JENTIK DALAM PEMBERANTASAN DEMAM BERDARAH DENGUE DI KABUPATEN BANTUL - , Hadi Pranoto, dr. Mubasysyir Hasanbasri, MA ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Dengue Hemorrhagic Fever (DHF) has become a problem in Bantul District and led to an extraordinary event. The government of Bantul had done frequent health education to people, been mobilizing them to implement breeding palce eradication (PSN), fogging, and carried out activity of free villages from 4 basic health problems, including DHF. Innovative measures taken by Bantul District government in prevention of DHF is empowering larva observer in family groups level (Jumantik RT) with the main task of periodically observing larva breeding sites, eradicating them, and reporting its results to the higher level such as Jumantik Desa. Jumantik Desa in their tasks were monitoring activity performance of Jumantik RT, reporting the result of larva breeding sites eradication to the higher authority, and evaluating its implementation. Objective: This study was aimed at evaluating the empowerment of Jumantik RT and Jumantik Desa in eradicating DHF in Bantul District. Method: A qualitative research with rapid assessment procedure (RAP) was used for this research. The number of subjects were 99.consisted those who were working in the field up to the decision makers. Data were collected by focus group discussion, in-depth interviews, observation and documents study. The study was located in six endemic DHF subdistricts. Results: Jumantik empowerment in eradicating DHF in Bantul District was begun by health cader recruitment to be Jumantik RT and Jumantik Desa. Recruitment was done by direct appointment of Dukuh based on the recommendation of Head of RT, PPKBD and Public Health Center. The teamwork of Jumantik was Head of RT, Head of the Ten Home Group, Dukuh, Team of DHF from sub-district and district of Bantul. The training process for Jumantik Desa was carried out by the Health Center of Bantul Districts, and for Jumantik RT by local village. The Jumantiks were equipped by the periodic larva eradication, flashlight, and leaflet of DHF and abate powder. Reward for them were budgeted from Bantul District in the form of monthly honorary. Jumantik empowerment had been successfully improving the absence of larva rate (ABJ). Conclusion: The community participation in the implemention of breeding place eradication (PSN) encouraged by Larva Observers empowerment has increased the absence of larva rate (ABJ)